Safety and Efficacy of Prolonged Use of Dalbavancin in Bone and Joint Infections - Morata, L. (Antimicrob Agents Chemother, 2019)
Dalbavancin is a lipoglycopeptide with potent activity against Gram-positive microorganisms, a long half-life, a favorable safety profile, and a high concentration in bone, which makes it an interesting alternative for treatment of osteoarticular infections. We performed a multicentric retrospective study of all patients with an osteoarticular infection (septic arthritis, spondylodiscitis, osteomyelitis, or orthopedic implant-related infection) treated with at least one dose of dalbavancin between 2016 and 2017 in 30 institutions in Spain. In order to evaluate the response, patients with or without an orthopedic implant were separated. A total of 64 patients were included. Staphylococcus epidermidis and Staphylococcus aureus were the most frequent microorganisms. The reasons for switching to dalbavancin were simplification (53.1%), adverse events (25%), or failure (21.9%). There were 7 adverse events, and no patient had to discontinue dalbavancin. In 45 cases, infection was related to an orthopedic implant. The implant material was retained in 23 cases, including that in 15 (65.2%) patients that were classified as cured and 8 (34.8%) that presented improvement. In 21 cases, the implants were removed, including those in 16 (76.2%) cases that were considered successes, 4 (19%) cases were considered improved, and 1 (4.8%) case that was considered a failure. Among the 19 cases without implants, 14 (73.7%) were considered cured, 3 (15.8%) were considered improved, and 2 (10.5%) were considered failures. The results show that dalbavancin is a well-tolerated antibiotic, even when >2 doses are administered, and is associated with a high cure rate. These are preliminary data with a short follow-up; therefore, it is necessary to gain more experience and, in the future, to establish the most appropriate dose and frequency.